Analysis of Media Mechanisms in Promoting Physical Activity Among the Elderly: Developing a Paradigmatic Model - Nour Mohammadi , Simin; Safania, Ali Mohammad; Farahani, Abolfazl; Naghshbandi, Seyed Salaheddin (Mental Health and Lifestyle Journal, 2026)
The national media, with its extensive influence and credibility, serves as an effective instrument for informing, cultivating public culture, and guiding society toward healthy and constructive behaviors. The present study aimed to analyze media mechanisms in promoting physical activity among the elderly and to develop a paradigmatic model. This research is applied in terms of purpose and descriptive–survey in nature with a quantitative approach. The data collection tool was a researcher-made questionnaire consisting of 43 items, designed based on theoretical foundations and prior research. The statistical population included all physically active elderly individuals over 60 years old in Tehran who engaged in moderate to vigorous physical activity for at least three days per week and 90 minutes per session. A purposive sampling method was employed, and data were collected through 128 valid questionnaires. The content validity of the questionnaire was confirmed by experts, and construct validity was verified through confirmatory factor analysis, convergent validity indices (AVE), and composite reliability (CR). The reliability of the instrument was also reported at an acceptable level using Cronbach’s alpha coefficient. Data were analyzed at both descriptive and inferential levels. The results indicated that media—particularly the national broadcasting network and mass media—play a significant role in informing, educating, cultivating public culture, and motivating the elderly to engage in physical activities. Furthermore, social media, by providing interactive platforms and facilitating experience sharing, complements traditional media in promoting an active lifestyle among the elderly. The paradigmatic model of the study demonstrated a good fit (GOF = 0.664), revealing that causal, contextual, and intervening conditions, through media strategies, can lead to outcomes such as the development of holistic health and increased participation of the elderly in sports activities.